Solving The Problem of Unconstrained Optimization Using Mathematical Programs - Nasiba Makhmudova (Web of Journals Publishing, 2023)
This article shows a method for solving optimization problems, which is widely used in economics. It is convenient to solve problems using the MathCAD software package. Today, it is necessary for a specialist to have sufficient competence in the field of innovative technologies. The article shows how to solve practical problems using MathCAD software.
Keywords: Optimization, modeling, income, MathCAD, mathematical model, algorithm.